Classification and summarization of solar photovoltaic MPPT techniques: A review based on traditional and intelligent control strategies - Mingxuan Mao; Lichuang Cui; Qianjin Zhang; Ke Guo; Lin Zhou; Han Huang (Energy Reports, 2020)
The output power-voltage (P-V) curve of a solar photovoltaic (PV) power system shows a single peak under an even irradiation environment, nevertheless, but often exhibits seriously nonlinear multi-peak characteristics under partial shading conditions (PSCs). Then, traditional maximum power point tracking (MPPT) control methods may fail to find the maximum power point (MPP). Many different MPPT control methods have been proposed to adjust the peak power output and improve the generating efficiency of the PV system. In this paper, the main MPPT techniques for PV systems are reviewed and summarized, and divided into three groups according to their control theoretic and optimization principles. Especially, the advantages and disadvantages of the MPPT techniques for PV system under PSCs are compared and analyzed. Finally, possible future research directions for MPPT are discussed.
Keywords: 330; Intelligence control methods; Maximum power point tracking; PV power system; Under partial shading conditions